The role of CD4+CD25+Foxp3+ regulatory T cells in the patchomechanism of transient hypogammaglobulinemia of infancy - Rutkowska-Zapała, Magdalena (2013)
Transient hypogammaglobulinemia of infancy is one of the most common primary humoral immunodeficiencies in children. The underlying basis of reduced serum immunoglobulins level and their subsequent mechanisms of normalization are still unknown. The main goal of this study was to determine new pathomechanisms underlying this immunodeficiency, as well as to establish new criteria/immunological parameters that would be useful in the differential diagnosis of THI and early-onset CVID. In this study the number of circulating CD4+CD25+Foxp3+ Treg cells and several parameters related to the generation and function of these cells were determined. Prospective clinical observations of children with THI revealed that initially increased Treg numbers decreased with age and reached the values observed in healthy subjects. The normalization of IgG levels in serum and withdrawal of clinical symptoms occuring with the decrease of the Treg number in the peripheral blood was observed. Functional evaluation of Treg cells performed in vitro has demonstrated their inhibitory effect on the production of IgG by B lymphocytes. However, the analysis of sequences of receptors for TGF-β encoding genes has not shown any mutations/polymorphisms that could be responsible for studied deficiency. The obtained data indicate the important role of Treg cells in the pathogenesis of THI (yet not CVID or SIgAD). Ev
Keywords: primary immunodeficiencies (PID); regulatory T cells (Treg); common variable immunodeficiency (CVID); transcription factor Foxp3; transient hypogammaglobulinemia of infancy (THI)